(untitled) (Revista Científica Compendium, 2020)
For 16 years the Jacinto Lara Center came to fill a gap in urban management in Barquisimeto and other cities of the state of Lara, Venezuela. Since its creation in 1994, it has been responsible for promoting strategic projects that required the interinstitutional concert to carry them out, taking into account the interdisciplinary complexity of urban phenomena. The experience has come to fruition in the formulation of multiple plans, programs, projects, technical assistance and execution of works that are distributed throughout the larense geography and, in particular, in Barquisimeto. The public company took on the challenge of implementing urban initiatives and did so in three areas: Habitat, related to integral housing development; Citizenship, modelling of citizen meeting spaces, and Heritage, revitalization of the built heritage. This assay is an overview of its unique institutional conception, its achievements and learnings in urban management, model experience for the country.